Positron Emission Tomography in Cerebral Amyloid Angiopathy: A Scoping Review - Marialuisa Zedde; Fabrizio Piazza; Rosario Pascarella (Applied Sciences)
Background/Objectives: Cerebral amyloid angiopathy (CAA) is one of the most prevalent small vessel diseases (SVDs). Its diagnostic criteria rely mainly on neuroimaging markers, in particular using Magnetic Resonance Imaging (MRI), as pathology-based diagnoses are only occasionally available. Amyloid PET is frequently used to assess parenchymal amyloid deposition in Alzheimer’s disease (AD), but amyloid tracers are not specific to vascular and parenchymal amyloids. The aim of this scoping review is to assess the usefulness of amyloid PET imaging in CAA. Methods: A systematic literature search was performed, aiming to assess amyloid PET performance in the following situations: (I) CAA-related intracerebral hemorrhage (ICH) and convexal subarachnoid hemorrhage; (II) pathology-proven CAA; (III) CAA-related inflammation; (IV) hereditary CAA. Results: A total of 52 studies were retrieved, including three systematic reviews, and from these, a specific selection was taken according to each objective, confirming the diagnostic value of amyloid PET added to MRI and clinical information in all the selected situations, although with some limitations. Conclusions: Amyloid PET reliably detects increased global and region-specific amyloid deposition in CAA patients, with a characteristic occipital-predominant pattern. Continued advancements in tracer development and imaging methodologies are needed to increase specificity.